Teori Big Five Personality dalam Ilmu Psikologi dan Relevansinya dengan Konsep Kepribadian Manusia Perspektif Al-Qur’an - Azhari, Khairul (UIN SUSKA RIAU, 2024)
This research discusses the concept of human personality contained in the Koran and after that the author reviews its relevance to the big five personality theory in psychology. In this research, the author will explain the concept of human personality in the Koran, then look at the big five personality theory and then review the relevance of the concept of human personality in the Koran with the big five personality theory. This research is library research and the method used is descriptive analysis with a qualitative approach. In the final results of this research, the author found that the big five personality theory contained five types of personality aspects discussed, namely Neuroticism, Extraversion, Openness to Experience, Agreeableness and Consistency. in the Neuroticism aspect it is relevant to human personality in the Koran, such as being sad, easily emotional, giving up and likes to complain, in the openness aspect it is relevant to the nature of being able to accept input from other people. The Extraversion aspect is relevant to the human attitude of always being cheerful, active and always enthusiastic. In the Agreeableness aspect, it is relevant to the nature of being humble, honest, fair and generous. The aspect of conscientiousness is also relevant to the human nature of being hardworking, diligent, persistent, ambitious and so on. Keywords: Big Five Personality theory. Psychology, Human Personality.